(untitled) (Research, Society and Development, 2022)
Teaching Sciences nowadays does not limit itself to presenting scientific content to the students. The students must comprehend the way through which science is constructed, and its socio-cultural, political, and human aspects. In other words, it is necessary to approach the Nature of Science. Studies indicate that it should be taught explicitly by the teacher, and so that happens, it is necessary to use instructional materials in which NOS is present. In this article, we present a study that had a goal to analyze Popular Science Texts published in the journal Ciência Hoje das Crianças, regarding the presence of aspects of NOS and indicating pathways towards its usage in teaching. The analysis was carried out through Bardin’s content analysis methodology. We have concluded that the analyzed TSD’s present principles of NOS not in an explicit way, but can be used by the teacher during the teaching process of NOS since this type of text written by scientists and contextualized in multiple areas of the Natural Sciences can provide a more integral vision on science, provided that it is used critically and reflexively.